Implementasi Teknik Steganography Pada File Gambar Dan Audio Dengan Menggunakan Metode LSB - Siti Rohayah (OKTAL : Jurnal Ilmu Komputer dan Sains, 2023)
Steganography is the art and science of writing hidden messages or hiding messages in a way so that apart from the sender and the recipient, no one knows or realizes that there is a secret message. The most important part of steganography is the level of security of the information it hides, which refers to the inability of third parties to reveal the existence of hidden information. The goal is to hide or obscure the existence of hidden messages or information. The Least Significant Bit algorithm became the most popular method in steganography. With the Least Significant Bit method, Steganography can be done by inserting messages into images and audio. This method is the simplest and most effective technique when compared to other methods. This study succeeded in displaying the secret messages in the image as well as the audio, and there was no significant change in both the quality (cover and stego) and the text and audio.